Nano Fe-C3N4-enhanced hydroxyl radical loop promotes organic matter decomposition in anoxic soils - Jian Chen; Ruirui Chen; Huan Deng; Jan Dolfing; Yifan Zhang; Xu Song; Shiying He; Yuanyuan Bao; Youzhi Feng (Journal of Environmental Chemical Engineering, 2026)

Rapid aerobic sludge granulation by short-term in-situ chitosan dosing: Performance, mechanism and microbial response - Fengfan Yu; Ruirui Wang; Yanhang Wang; Mengjie Qian; Jintao Sun; Jinwen Song; Jinte Zou; Jun Li (Bioresource Technology, 2026)

Bioinformatics analysis and differential tissue expression of the IGFBP4 gene in beef cattle - Ruirui Song; Bingzhi Li; Sihu Wang; Maryam Alenize; Yanqing Zhao; Aaishah M. H. Kaabi; Afnan O. Deebani; Wasimah AlShammari; Dalal Alenizi; Dalal Alardan; Wenzhen Zhang (Protoplasma, 2026)

Super-resolution multimodal spatial transcriptomics reveals an ovoid stem cell niche structuring de novo shoot regeneration - Xiehai Song; Shaoman Zhang; Zhiliang Yue; Yongqi Liu; Shanshan Chen; Yani Niu; Yan Shi; Hengjia Yang; Jiahao Xu; Yuanyuan Miao; Meizhi Xu; Yingxue Zhou; et al. (Molecular Plant, 2026)

Restorative coastal spaces: How spatial typologies and landscape elements shape psychological and physiological responses - Ruirui Zhu; Ruixin Xue; Yu Song; Jie Xiong; Ian Mell; Weijun Gao (Building and Environment, 2026)

Enhancement of calcium oxide on hydrogen production and degradation of polylactic acid microplastics in anaerobic fermentation - Xiaoxuan Zhu; Ruirui Shang; Xi Yang; Chuanzheng Song; Hui Mu; Chunhui Zhao; Huanhuan Guo; Yongfang Zhang (Journal of Environmental Management, 2026)

Atrazine-induced hippocampal neurotoxicity: Involvement of Drp1-mediated mitochondrial fission - Jingran Yang; Ling Qi; Cheng Zhang; Ruirui Ding; Haoran Bi; Peng Li; Zhipeng Qi; Qiao Niu; Weiyi Song; Jianan Li (Chemico-Biological Interactions, 2025)

High-efficiency and stable perovskite solar cells via bidentate chelation for facet-engineered growth of FAPbI3 (111) crystals - Song Zhang; Yucong Zhou; Zhitao Shen; Yingying Li; Jian Song; Yicong Gao; Zezhi Wang; Bohao Zhang; Chong Chen; Rong Liu; Ying Liu; Ruirui Cao; et al. (Chemical Engineering Journal, 2025)

Long-term reconstruction of NO2 photolysis rate coefficients using machine learning and its impact on secondary pollution: A case study in a megacity of the Sichuan Basin, China - Tong Li; Song Liu; Dongyang Chen; Ruirui Zhang; Hefan Liu; Danlin Song; Qinwen Tan; Hongbin Jiang; Li Zhou; Fumo Yang (Atmospheric Pollution Research, 2025)

Layered double hydroxides-engineered biochar for selective phosphate recovery by flow-electrode capacitive deionization - Jingke Song; Xin Zhao; Ruirui Liu; Songsong Zhi; Ruixue Han; Jiangzhou Xie; Jianhui Sun; Kai Jiang; Dapeng Wu (Journal of Environmental Chemical Engineering, 2025)

Energy absorption behavior of a bottom-supported thin-walled steel tube impacted by rockfall - Fuyou Huang; Luqing Zhang; Jian Zhou; Zhenhua Han; Song Wang; Ruirui Li (Natural Hazards, 2025)

Nonlinear interactions of internal waves and the force of internal solitary waves on small - Diameter cylinders - Qian Liu; Zhao Song; Huan Mei; Ruirui Zhang; Zhenzhen Nong; Daiyu Zhang (Ocean Engineering, 2025)

Depositional evolution of nearshore fringing reefs in the Changpi region, Hainan Island: assessing the impact of siliciclastic influx on reef development - Maosong Ye; Lijuan Shao; Ruirui Song; Weihua Liao; Qiaozhu Pang; Hongfei Xu (Frontiers in Marine Science, 2025)
Nearshore fringing reefs have been shown to establish and accrete within sediment-laden coastal environments over millennial timescales. However, the mechanisms governing the evolution of turbid-water reefs remain inadequately understood. This study focuses on a fringing reef in the Changpi (CP) region along the eastern coast of Hainan Island, China. Sedimentological and geochronological analyses of four drill cores provided the first comprehensive growth history for this marginal reef setting through a systematic reconstruction of its developmental chronology, architectural framework, and ecological characteristics. Radiocarbon dating reveals reef initiated at about 7,400 cal yr BP and ceased accretion after 4,000 cal yr BP. By integrating core observations, thin-section petrography, and X-ray diffraction results, five distinct lithofacies were identified. These lithofacies exhibit varying degrees of mixing between siliciclastic and carbonate components, revealing that the reef system was periodically influenced by terrigenous siliciclastic input. The vertical accretion of the CP reef underwent three primary stages: (1) colonization stage (7,400-6,400 cal yr BP), characterized by well-preserved coral assemblages in high-energy, clear-water conditions with relatively low accretion rates (ca 0.35 mm/yr) and gradual coral diversification; (2) turbid stage (6,400-5,500 cal yr BP), marked by rapid terrigenous clastic deposition that produced persistent turbidity, leading to accelerated accretion rates (up to 6.29 mm/yr) and reduced coral diversity; and (3) stabilization stage (5,500-4,000 cal yr BP), during which stabilized siliciclastic input restored clear-water conditions, supporting renewed coral growth at moderate accretion rates (ca 2.70 mm/yr). This case study demonstrates that terrestrial sediment fluxes can exert a greater influence on nearshore reef trajectories than sea-level changes, particularly in regions or periods characterized by high sediment input. As suggested by the findings, this underscores the necessity of integrated coastal zone management strategies aimed at reducing agricultural runoff and controlling construction sediment to enhance reef resilience.

Multi-field Coupling Simulation of Impact of Temperature and Density of Heat Injection Well on Carbon Budget during Hydrate Exploitation in Qilian Mountain Permafrost Region - Zhenhua Han; Ruirui Li; Luqing Zhang; Jian Zhou; Song Wang (Journal of Earth Science, 2024)

Synthesis of iron-manganese bimetallic materials supported by activated carbon and application of activated persulfate in the degradation of soil contaminated by crude oil - Jin Zheng; Chunyang Gao; Xianyuan Du; Hongkun Chen; Ruirui Han; Jiacai Xie; Dexun Zou; Quanwei Song; Zhansheng Wang; Xingchun Li (Environmental Research, 2024)

Numerical Determination of Anisotropic Permeability for Unconsolidated Hydrate Reservoir: A DEM–CFD Coupling Method - Ruirui Li; Zhenhua Han; Luqing Zhang; Jian Zhou; Song Wang; Fuyou Huang (Journal of Marine Science and Engineering, 2024)
Natural gas hydrate (NGH) is considered as a type of clean energy to replace coal and oil. During exploitation, permeability is one of the key parameters controlling production efficiency, reservoir stability, and greenhouse gas sequestration. Limited by experimental and numerical simulation tools, in current research, the directionality of permeability is usually ignored. In this work, a DEM–CFD coupling simulation method is developed to compute the anisotropic permeability. The sedimentary process of reservoir sediments is reconstructed, enabling the acquisition of numerical models that possess pore structures consistent with the actual fabric characteristics. The fluid transport process in various directions can be simulated with a finite element method. Taking the natural gas hydrate reservoir in the Shenhu area of the South China Sea as an example, the proposed method is validated and applied to explore the effect of compaction stress on permeability anisotropy. With the increase in compaction stress, the permeability anisotropy exhibited a rapid initial increase, followed by a sustained stabilization. The primary cause is the rearrangement of sediment particles. The non-spherical particles are driven to align in a predominantly horizontal orientation, thereby enhancing anisotropy. The proposed method provides a tool for the efficient exploitation of hydrate resources.

Effect of Hydrate Saturation on Permeability Anisotropy for Hydrate-Bearing Turbidite Sediments Based on Pore-Scale Seepage Simulation - Ruirui Li; Zhenhua Han; Luqing Zhang; Jian Zhou; Song Wang (Journal of Marine Science and Engineering, 2024)
The permeability of natural gas hydrate (NGH) turbidite reservoirs typically exhibits significant anisotropy, with anisotropy being a crucial basis for evaluating reservoir production. The presence of hydrates, as a crucial constituent of the solid framework, not only impacts the overall permeability but also influences the permeability anisotropy. To investigate the saturation sensitivity of permeability anisotropy, a series of simulations are performed by integrating particle flow and computational fluid dynamics methods to construct the homogeneous and layered numerical samples and compute the evolution of permeability anisotropy. It is shown that the permeability is isotropic for homogeneous sediments and the isotropy remains unchanged regardless of variations in hydrate saturation. The permeability of layered sediments, in contrast, exhibits significant anisotropy due to the presence of dominant channels within the coarse layer. For uniformly distributed hydrates, the more effective blockage in coarse layers results in a reduction in anisotropy. While for preferentially distributed hydrates, the excess blocking of coarse layers makes the dominant channels transfer to the fine layers, the further blocking causes a U-shaped anisotropy–saturation curve characterized by a decrease–increase transformation. During the reservoir production process, the preponderance channels blocked by hydrates will be cleared and the horizontal permeability will significantly increase. As a result, the production efficiency of horizontal wells may exceed expectations. The findings offer a parameter support for production estimation and environmental assessment.

Mg Fe- layered double hydroxides (LDHs) modified electrode enhanced capacitive deionization for simultaneous phosphorus recovery and copper ions removal - Jingke Song; Chenyang Li; Xin Zhao; Ruirui Liu; Ruixue Han; Kai Jiang; Meiqing Shi; Dapeng Wu (Journal of Environmental Chemical Engineering, 2024)

Effects of oyster shells on maturity and calcium activation in organic solid waste compost - Wanlin Song; Yang Zeng; Jiali Wu; Qian Huang; Ruirui Cui; Derui Wang; Yuxue Zhang; Min Xie; Dawei Feng (Chemosphere, 2023)

Rapid discrimination of the identity of infant formula by triple-channel models - Nasi Ai; Ruirui Liu; Xuelu Chi; Zheng Song; Yiwei Shao; Yanmei Xi; Tong Zhao; Baoguo Sun; Jianbo Xiao; Jianjun Deng (Food Chemistry, 2023)

Fabrication and application of molecularly imprinted polymer doped carbon dots coated silica stationary phase - Peijun Chai; Xuhui Geng; Ruirui Zhu; Wenpu Wu; Xuesong Wang; Jinhua Li; Longwen Fu; Hongdan Wang; Wanhui Liu; Lingxin Chen; Zhihua Song (Analytica Chimica Acta, 2023)

Cadmium accumulation and isotope fractionation in typical protozoa Tetrahymena: A new perspective on remediation of Cd pollution in wastewater - Ruirui Wang; Zhiqiang Zhu; Wenhan Cheng; Chuanyu Chang; Xiaoyuan Song; Fang Huang (Journal of Hazardous Materials, 2023)

Reshaping of the soil microbiome by the expansion of invasive plants: shifts in structure, diversity, co-occurrence, niche breadth, and assembly processes - Changchao Li; Huaizhi Bo; Bingzhong Song; Xiaocui Chen; Qingqing Cao; Ruirui Yang; Shuping Ji; Lifei Wang; Jian Liu (Plant and Soil, 2022)

Design of supercontinuum laser hyperspectral light detection and ranging (LiDAR) (SCLaHS LiDAR) - Guoqing Zhou; Xiang Zhou; Youjian Song; Donghui Xie; Long Wang; Guangjian Yan; Minglie Hu; Bowen Liu; Weidong Shang; Chenghu Gong; Cheng Wang; Huaguo Huang; et al. (International Journal of Remote Sensing, 2021)

Antisense oligonucleotide technology can be used to investigate a circular but not linear RNA-mediated function for its encoded gene locus - Zhenxing Song; Ruirui Jia; Mingfeng Tang; Fei Xia; Haiyang Xu; Zhengguo Li; Chuan Huang (Science China Life Sciences, 2021)

The Dysfunction of the Cerebellum and Its Cerebellum-Reward-Sensorimotor Loops in Chronic Spontaneous Urticaria - Yuming Wang; Jiliang Fang; Ping Song; Yan Bao; Wenwen Song; Jiao Liu; Courtney Lang; Kristen Jorgenson; Minyoung Jung; Dong Shen; Shasha Li; Ruirui Sun; et al. (The Cerebellum, 2018)

Application of the CRISPR/Cas9 system in Dioscorea zingiberensis - Shan Feng; Wei Song; Ruirui Fu; Hong Zhang; Anran Xu; Jiaru Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

The relationship between microvasculature in white matter hyperintensities and cognitive function - Jianzhong Sun; Xinfeng Yu; Yerfan Jiaerken; Ruirui Song; Peiyu Huang; Chao Wang; Lixia Yuan; Yingying Mao; Yang Guo; Hualiang Yu; Minming Zhang (Brain Imaging and Behavior, 2017)

Chimeric DNA vaccines encoding Eimeria acervulina macrophage migration inhibitory factor (E.MIF) induce partial protection against experimental Eimeria infection - Xiaokai Song; Ruirui Zhang; Lixin Xu; Ruofeng Yan; Xiangrui Li (Acta Parasitologica, 2015)
Chimeric DNA vaccines co-expressing Eimeria acervulina macrophage migration inhibitory factor (E.MIF) and chicken IL-2 (IL-2) or interferon-γ (IFN-γ) were constructed and their efficacies against E. acervulina were evaluated. The open reading frame (ORF) of E.MIF was cloned from E. acervulina merozoites and subcloned into the eukaryotic expression vector pVAX1 with chicken cytokine gene IFN-γ or IL-2 to construct the DNA vaccines pVAX-E.MIF-IFN-γ, pVAX-E.MIF-IL-2 and pVAX-E.MIF. The in vivo transfection of the target genes was detected by use of reverse transcription polymerase chain reaction (RT-PCR) and Western blot. Immunizations were carried out by vaccinating chickens twice with a dose rate of 100 μg intramuscularly. Seven days post second immunization, all chickens except the unchallenged control group were challenged orally with 1 × 105 sporulated oocysts of E. acervulina. Seven days later, the duodenum was collected. The results showed that the target genes were expressed effectively in vivo. DNA vaccines and the recombinant E.MIF protein could alleviate body weight loss and duodenal lesions significantly compared to the control groups. Furthermore, pVAX-E.MIF-IL-2 and pVAX-E.MIF-IFN-γ induced anticoccidial indexs (ACIs) of 179.12 and 170, respectively, which were significantly higher than that of pVAX-E.MIF (ACI = 162.31). Our results demonstrated that E.MIF is a potential vaccine candidate against E. acervulina and chicken IFN-γ or IL- 2 may be used as genetic adjuvants to improve the efficacies of DNA vaccines against avian coccidiosis.

Study of the comprehensive risk analysis of dam-break flooding based on the numerical simulation of flood routing. Part I: model development - Ruirui Sun; Xiaoling Wang; Zhengyin Zhou; Xuefei Ao; Xiaopei Sun; Mingrui Song (Natural Hazards, 2014)

Study of the comprehensive risk analysis of dam-break flooding based on the numerical simulation of flood routing. Part II: Model application and results - Zhengyin Zhou; Xiaoling Wang; Ruirui Sun; Xuefei Ao; Xiaopei Sun; Mingrui Song (Natural Hazards, 2014)